Repetitive transcranial magnetic stimulation may promote the reversion of mild cognitive impairment to normal cognition - Guo, Zhiwei; Jiang, Yi; He, Jiayuan; Jiang, Ning (Frontiers in Psychiatry, 2025)
PurposeThis study aimed to investigate the potential effects of repetitive transcranial magnetic stimulation (rTMS) on the reversion of mild cognitive impairment (MCI) to normal cognitive function and to elucidate the underlying mechanisms.MethodsThe study enrolled 25 MCI participants, who underwent a 10-day of rTMS treatment and an 18-month follow-up, along with 15 healthy subjects. Participants with MCI were categorized into MCI reverters (MCI-R) and MCI maintainers (MCI-M). We assessed differences in baseline cognitive performance, functional connectivity, and changes of cognitive functions after rTMS between MCI-R and MCI-M to identify possible predictors of reversion of MCI and explore the neural modulation mechanisms.ResultsMCI-M exhibited more severe cognitive impairments across more domains, particularly in language function (p < 0.05). Functional connectivity was more severely damaged in MCI-M participants, notably within the default mode network (DMN), executive control network (ECN), and frontoparietal network (FPN). After rTMS therapy, MCI-R participants demonstrated more significantly improved immediate and delayed recall memory scores (p < 0.05). These memory function changes and baseline functional connectivity of DMN, ECN, and FPN were predictive of the reversion of MCI.ConclusionsThe efficacy of rTMS in memory function may promote the reversion of MCI to normal cognition, with the functional connectivity of DMN, ECN, and FPN playing a crucial important role. The severity of cognitive impairment and functional connectivity damage correlated with the likelihood of the reversion of MCI to normal cognition, underscoring the importance of early rTMS intervention for dementia prevention.